Technology Utilization in Teaching and the Work Performance of Junior High School Teachers - Dolandolan, Petra D.; Agatep, John Lennon E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the technology utilization in teaching and work performance of Junior High School Teachers in Zambales. The findings of the study revealed that the majority of the teacher-respondents are female, in their early adulthood, married, with earned units in MA, Mathematics major, Mathematics teaching load, with adequate years in service, Teacher I, and have attended numerous trainings related to the use of technology. The teacher-respondents perceived the use of ICT in their teaching to be highly utilized. Teachers performed very satisfactorily in their job using ICT in teaching. ICT training attended was found to significantly influence utilization across most dimensions, including planning, monitoring, implementation, productivity, and enrichment. Despite this high utilization and Very Satisfactory job performance, the study found no significant relationship between the utilization of ICT in teaching and the overall work performance of teachers, suggesting that high ICT use alone does not predict superior job outcomes. The proposed model plan has been developed to address difficulties in the technology utilization in the teaching of teachers.